Eksperimen Pembelajaran Matematika dengan Strategidiscovery Learning Dan Group Investigation Terhadap Hasil Belajar Matematika Ditinjau Dari Keaktifan Siswa Di SMP Negeri 1 Teras - Mayasri, Atik (2016)
Education is process and there are components to most influence for the teacher, students, learning media, the source of learning, and society. The result of learning from the learning process are needed to know the performance of leaning purposes such as cognitive ability, affective ability, and psychometric. The data of the result from learning mathematic of student seventh grade of Junior High School in Teras is not including maximum. This cause of internal and external factor, beside that being active of students can influence the result of learning mathematic. The aim of observation is to analyses the effects of using learning strategies of investigation group and discovery learning base on the result of learning mathematic process, to analyses the effects of being active of students base on the result of learning mathematic process, to analyses of interaction between learning strategies of investigation group and discovery learning with being active on result of learning mathematic. The types base on scientific quantitative. Design of observation is quasi experimental. The technique of analysis data is using analysis variants two ways. Base on the result of observation, can conclude there are influence of strategies of group investigation and discovery learning for the result of learning mathematic with significant level 5%, to influence the level of being active in result of learning mathematic with significant level 5%, for the interaction between group investigation and discovery learning with significant level 5%.